2021
DOI: 10.1210/clinem/dgab675
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Diabetes Mellitus and the Risk of Herpes Zoster: A Systematic Review and Meta-analysis

Abstract: Context Individuals with diabetes mellitus (DM) are susceptible to various infections. Objective We estimated the risk of herpes zoster (HZ) among individuals with DM compared to individuals in the general population. Data Sources We searched the PubMed, Embase, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trails, Cumulativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Common risk factors for HZ are age > 50 years, immunosuppression, infections, and mental stress [14]. A meta-analysis of 16 studies till January 2021 confirmed that patients with diabetes mellitus also have a higher risk (pooled relative risk: 1.38; 95% confidence interval (CI): 1.21-1.57) [15].…”
Section: Epidemiologymentioning
confidence: 99%
“…Common risk factors for HZ are age > 50 years, immunosuppression, infections, and mental stress [14]. A meta-analysis of 16 studies till January 2021 confirmed that patients with diabetes mellitus also have a higher risk (pooled relative risk: 1.38; 95% confidence interval (CI): 1.21-1.57) [15].…”
Section: Epidemiologymentioning
confidence: 99%
“…Hung et al analyzed 16 studies and discovered that patients with DM had a higher risk of HZ than did the general population, the relative risk was 1.38. The authors thus suggested that the HZ vaccine be considered for patients with DM [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since our search of the database identified no relevant studies that included immunocompromised patients, though, further research is needed to assess the efficacy of these agents in such population. For example, another recent meta-analysis found that individuals with diabetes mellitus (DM) were at greater risk of HZ than general population (pooled relative risk [RR]: 1.38; 95% CI, 1.21–1.57) as well as a dose-response association between age and the risk of HZ within the DM population [ 91 ]. Similar results have also been reported in the adult population for individuals with diabetes, who experienced a higher adjusted risk of HZ (hazard ratio = 1.45; 95% CI: 1.43 to 1.46) and higher adjusted odds of persistent post-zoster pain (OR = 1.18, 95% CI: 1.13 to 1.24) [ 92 ].…”
Section: Discussionmentioning
confidence: 99%